Differential Impact of Sharecropping on Time Allocation and Risk Transfer in Farming: An Islamic Economic Perspective - Ihsandi, Aslan Deri (SAFE-Network, 2024)
This study presents a quantitative exploration of the influence of sharecropping on the allocation of time and risk transfer in farming practices. Through a causal associative research design, the study identifies various factors of influence on the dependent variable, applying an Ordinary Least Squares (OLS) regression analysis on survey data. The results provide intriguing insights into farmers' decision-making and preferences concerning cooperation models based on land ownership status. Our findings reveal that shareholder farmers, who farm lands belonging to others, exhibit preferences distinct from owner-farmers for cooperative models. Similarly, those cultivating both others' and their own lands demonstrate unique inclinations towards different cooperative models compared to owner-farmers. The results also emphasize the significance of risk perceptions in these preferences. A significant tendency was observed among farmers to allocate more time to farming when they are relieved of risk entirely in an agricultural management scenario, particularly in long-duration collaborations. In contrast, owner-farmers and those cultivating both their own and others' land exhibited a more cautious approach, agreeing to share risks but within limited periods of cooperation. These findings contribute to a nuanced understanding of the effects of sharecropping on farmers' time management and risk-allocation decisions, providing significant implications for agricultural policy and practices. Further research should delve into the psychosocial factors that influence these preferences to enable the creation of more equitable and efficient farming systems.